2011
DOI: 10.1016/j.respol.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Subsidy and networking: The effects of direct and indirect support programs of the cluster policy

Abstract: Industrial clusters have attracted considerable attention worldwide for their expected contribution to regional innovation. Recently, policymakers in various countries have developed specific cluster policies. However, there exist few empirical studies on cluster policies. In this study, we use original questionnaire data to empirically evaluate the Industrial Cluster Project (ICP) initiated by the Ministry of Economy, Trade and Industry in 2001. We address two research questions on the effect of the ICP: are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(105 citation statements)
references
References 49 publications
(27 reference statements)
2
94
0
4
Order By: Relevance
“…They did not find a significant effect of cluster participation on a firm's R&D productivity, but rather showed that participating firms collaborating with partners outside the cluster were more productive in terms of patent output. In further research focused on the same cluster program, Nishimura and Okamuro (2011b) discovered that cluster participants making use of indirect support measures within the program (e.g. information and consulting services, participating in events) significantly expanded their network activities, whilst direct R&D subsidies had only a weak effect.…”
Section: Clusters and Innovation Policymentioning
confidence: 99%
“…They did not find a significant effect of cluster participation on a firm's R&D productivity, but rather showed that participating firms collaborating with partners outside the cluster were more productive in terms of patent output. In further research focused on the same cluster program, Nishimura and Okamuro (2011b) discovered that cluster participants making use of indirect support measures within the program (e.g. information and consulting services, participating in events) significantly expanded their network activities, whilst direct R&D subsidies had only a weak effect.…”
Section: Clusters and Innovation Policymentioning
confidence: 99%
“…In Japan, MEXT implemented the Knowledge Cluster Initiative (KCI) and the City Area Program (CAP) in 2002, which were reorganized and integrated into the Regional Innovation Cluster Program in 2010, while METI (Ministry of Economy, Trade and Industry) carried out another cluster policy, Industrial Cluster Project ( [18,19]). In the MEXT programs, universities and public research institutes play a central role in the clusters as the cores of research collaboration with private firms.…”
Section: Cluster Policies In Japanmentioning
confidence: 99%
“…Moreover, some recent studies empirically evaluate the effects of cluster policies on participant firms using micro data, such as [13][14][15] for Germany, [16,17] for France, and [18,19] for Japan. There is a vast amount of literature on the economies of agglomeration (e.g., [16] and on the clustering process or mechanism in an established cluster (e.g., [1]).…”
Section: Introductionmentioning
confidence: 99%
“…As with supply chains, collaboration in industrial clusters requires strategic alignment, selection of common performance measures, agreement on a shared set of principles and rules, as well as the development of coordination capabilities (Sölvell et al, 2003;Afsarmanesh et al, 2009). Nishimura & Okamuro (2011) found that indirect coordination support helps to build up new collaborative networks within clusters. The authors also suggest that participating in meetings and events and using coordination and advisory services enhance several dimensions of a company's performance.…”
Section: Performance Management In Industrial Clustersmentioning
confidence: 99%